(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: The study aimed to describe clinical and paraclinical symptoms of tinea pedis among small business owners in Nghe An province. Methods: A descriptive method was employed. Results: The prevalence of tinea pedis in the study subjects was 15.8% (124/787), including 97 cases of simple nail lesions and 20 cases of skin lesions. 95.2% of the people had clinical nail color change, including yellow (32.3%), black (25.3%). The most common lesions occurred on both big toes, in which 80.8% were on the left big toe and 70.2% on the right big toe. Lesions on the lateral and distal edges were the most common clinical forms with a rate of 84.6%. The basic types of lesions were nail dystrophy (86.5%), nail separation (61.8%). In the interdigital space, the most common lesions were white, crumbly lesions (18/21). Lesions in the interdigital space accounted for (77.8%), and scaly skin was the basic lesion. The positive rate through direct testing and culture was 55.56% and 100% respectively. Conclusions: Clinical lesions were mainly changes of nail color. Skin lesions were common in the interdigital space of the big toe. The positive rate through direct testing in 20% KOH was 55.56%, and through fungal culture in Saboraud medium was 100.0%.